Multi-Channel perspective of value in the service dominant logic of Marketing - Brambilla, Flávio Régio (2013)
The new logic of market(ing) action proposed in the Service Dominant Logic (SDL) by Vargo and Lusch (2004) focus service provision and value co-creation. In multi-channel perspective little is discussed. This relation among topics constitutes a gap for further research. Different systems of buyer-supplier relationship edge the question of integration. How to integrate the channells to generate greater value-in-use? How to provide best service system? Trying to answer this question, the suggestion is for an approach based in the SDL, as an oportunite to develop new propositions and to find solutions for some of marketing theories gaps that can better integrate the area of study. Understanding the SDL concepts and defining new patterns of analysis makes possible to study the multi-channel co-creative interaction among agents. Build as a theoretical paper, the study deals with some of the SDL and co-creation questions.